Remittances and the Brain Drain: Skilled Migrants Do Remit Less! - Yoko Niimi; Caglar Ozden; Maurice Schiff (Asian Development Bank (ADB), 2008)
It has been argued that the adverse impact of skilled versus unskilled labor migration can be mitigated or even offset by the fact that skilled migrants remit more than unskilled ones. This paper contributes to the much debated and so far unresolved related issue of whether remittances actually increase with migrants' level of education. The determinants of remittances considered include migration levels and rates; migrants' education level; and source countries' income, financial sector development, and expected growth rate. The estimation takes potential endogeneity into account, an issue not considered in the few existing studies on this topic. Our main finding is that remittances decrease for migrants with tertiary education. This provides an additional reason for source countries to prefer unskilled to skilled labor migration. Moreover, as predicted by our model, remittances increase with source countries' level and rate of migration, financial sector development and population, and decrease in per capita income and expected growth rate.
hdl:11540/1787
Keywords: 330; Rücküberweisungen; Migranten; Bildungsniveau; Brain Drain; Migrationsforschung; Wirtschaftsstufentheorie; Welt; Entwicklungsländer